Mixed metal oxide anodes for electrochemical oxidation of phenolic pollutants - Wu, Weiyi (2017)
Nowadays, recalcitrant organic pollutants have been continuously released into the natural and engineered water system. Their presence could hinder the biological treatment of water and wastewater. Electrochemical oxidation (EO) has emerged as a promising method to remove recalcitrant organics by employing electron as the clean reagent. The nature of anode material is found to be crucial for the success of this technology, and antimony-doped tin dioxide (SnO2-Sb) anode is of particular interests due to its high oxygen evolution potential and cost effectiveness. In this study, two kinds of modified SnO2-Sb anodes were fabricated using pulse electrodeposition method. Their electrocatalytic activities were evaluated through electrochemical oxidation of phenol and bisphenol A (BPA), with the effects of operating parameters such as solution pH, applied current density and type of supporting electrolyte. The modified SnO2-Sb electrodes exhibited higher OEP and improved electrochemical stability than conventional SnO2-Sb electrode fabricated by thermochemical decomposition. A comparative study was also carried out on the electrochemical oxidation of bisphenol A (BPA) by the modified SnO2-Sb electrodes and a commercial boron-doped diamond (BDD) electrode. Comparing with BDD, the modified SnO2-Sb electrodes showed the potential for industrial wastewater treatment due to their versatile electrocatalytic performances in different types of wastewaters. The study of reaction mechanisms showed that hydroxylation, oxidation and ring-opening reactions were involved in BPA degradation.